Design Of An Expert System To Diagnose Diseases In Onion Plants Using The Web-Based Dempster Shafer Method - Suryadin, Suryadin; Nur Fitrianingsih; Ita Fitriati (Engineering: Journal of Mechatronics and Education, 2024)
This study aims to design a website-based shallot disease expert system and determine the feasibility level of the website. The final result of this research is an expert system for diagnosing diseases in shallot plants using the Dempster Shafer method based on a case study web at the Monta District Agriculture UPTD which has been tested for feasibility. This research uses the R&D method with the Waterfall model. The stages in this study include five stages, namely (1) requirements stage, (2) design, (3) coding, (4) program testing, and (5) maintenance. with a sample of shallot farmers in the District of Monta, as many as 25 people were counted in small-group trials and large-group trials. The instrument used is a Questionnaire containing questions, with Data Analysis Techniques using a Likert scale. The results of this study are (1) an expert system for diagnosing diseases in shallot plants using the Dempster Shafer method based on a web case study at the UPTD Agriculture, Monta District; (2) the quality of the designed website-based shallot disease expert system is included in the very feasible category in terms of content and in terms of appearance, this is based on website feasibility assessments from material experts with a percentage of 93.3% and user ratings with a percentage of 95.5%, an expert system for diagnosing diseases in shallot plants using the web-based Dempster Shafer method in a case study at the Monta District Agriculture UPTD was declared very feasible to use.